Tell it like it is : a guide to clear and honest writing - Clark, Roy Peter (Little, Brown Spark, 2023)
"In Tell It Like It Is, bestselling author, writing coach, and teacher Roy Peter Clark offers a succinct and practical guide to writing with clarity, honesty, and conviction. By analyzing stellar writing samples from a diverse collection of public writers, Clark highlights and explains the tools journalists, scientists, economists, fact-checkers, even storytellers use to engage, inform, and hook readers, and how best to deploy them in a variety of contexts"--